2020
DOI: 10.1029/2019gl085721
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Lithospheric Deformation in Eastern Tibet Inferred From Seismic Anisotropy

Abstract: Mechanisms for uplift and deformation of the Tibetan Plateau remain vigorously debated; hypotheses include stepwise growth, distributed thickening, and crustal channel flow, each with a distinct anisotropic signature. We have developed a new azimuthally anisotropic shear velocity model for the lithosphere beneath eastern Tibet, based on ambient noise tomography from 643 seismic stations. In our model, the Tibetan upper crust is characterized by strong anisotropy with fast axes that correlate with surface geolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(64 citation statements)
references
References 66 publications
12
46
0
Order By: Relevance
“…These results suggest that low‐ Q Lg anomalies are connected in spite of strong inhomogeneity, probably indicating complicated connections for crustal material flow. The inhomogeneous crustal flow was also suggested by seismic anisotropy investigations (X. Bao et al., 2020; H. Huang et al., 2010, Huang, Wang, Xu, Ding et al., 2015; W. Wei et al., 2013). W. Wei et al.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…These results suggest that low‐ Q Lg anomalies are connected in spite of strong inhomogeneity, probably indicating complicated connections for crustal material flow. The inhomogeneous crustal flow was also suggested by seismic anisotropy investigations (X. Bao et al., 2020; H. Huang et al., 2010, Huang, Wang, Xu, Ding et al., 2015; W. Wei et al., 2013). W. Wei et al.…”
Section: Discussionmentioning
confidence: 66%
“…These regions are characterized by intense crustal deformation, intricate fault systems, and rough topography, which may result in remarkable Lg‐wave scattering and contribute to the low‐ Q Lg anomalies observed near major faults, including the Xianshuihe, Xiaojiang, Lijiang, and Sagaing faults (Wu et al., 2007). However, many studies have reported anomalies of high Poisson’s ratio, low S ‐wave velocity, and high conductivity within the crust in these regions (D. H. Bai et al., 2010; X. Bao et al., 2020; X. W. Bao et al., 2015; H. P. Chen et al., 2016; M. Chen et al., 2014; Q. Y. Liu et al., 2014; Qiao et al., 2018; Sun et al., 2012, 2014; W. L. Wang et al., 2017). The strong Lg attenuation obtained in this study also coincides with these anomalies, which seems to indicate that the intrinsic attenuation associated with thermal status and partial melting is an important origin of the Lg‐wave dissipation, in addition to the scattering effects.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the early phase of the India‐Asia continental collision, the pre‐existing CWZs were reactivated and developed a series of thrust faults and crustal folds in the eastern Tibetan Plateau (Burchfiel et al., 1995; Hubbard & Shaw, 2009; Jia et al., 2010). The crust and lithosphere mantle coherently deformed in the form of pure shear (Bao et al., 2020). By late Cenozoic, a thick partially molten mid‐lower crust layer with low viscosity and low density is generated in the Songpan‐Ganzi crust (Bai et al., 2010; Diao et al., 2018; Jia et al., 2014; Li et al., 2009; Liu et al., 2014; Wang et al., 2018; Yang et al., 2012; Zhang et al., 2014; Zhao et al, 2012, 2013).…”
Section: Discussionmentioning
confidence: 99%